Stylistics Of The Quran In A Scientific Perspective: Bassam Saeh's Formulative Offer In Learning Balaghah - Aulia Rahman, Rifqi; Mellyana, Mellyana; Mukromin, Mukromin (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
This study aims to examine the pedagogical approach to balāghah (Arabic rhetoric) as presented by Bassam Saeh in his book Bahasa al-Qur’an: Mukjizat atau Sekadar Kegeniusan (The Language of the Qur'an: Miracle or Mere Genius). Balāghah plays a crucial role in uncovering the beauty and rhetorical power of the Arabic language, especially in understanding the stylistic depth of the Qur’an. Using a qualitative descriptive method and a library research approach, this study analyzes how Saeh reformulates balāghah pedagogy in a contemporary educational context. The findings reveal that Bassam Saeh offers three principal approaches to balāghah instruction: (1) contextual analysis of structure and meaning in Qur’anic verses; (2) rational and reflective interpretation of stylistic elements; and (3) linguistic critique grounded in descriptive and scientific analysis. He emphasizes the importance of understanding the interplay between form and meaning, as well as the significance of historical and linguistic context in interpreting the Qur’anic message.These approaches contribute to the development of a balāghah curriculum that is not only normative and theoretical, but also applicable, critical, and responsive to the intellectual needs of modern learners. The study is expected to serve as a reference for designing text-based and critical-thinking-oriented instructional models in Arabic rhetoric and Qur’anic studies.